2012
DOI: 10.1177/1090820x12455190
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of High-Intensity Focused Ultrasonography for Noninvasive Body Sculpting: 24-Week Data From a Randomized, Sham-Controlled Study

Abstract: This HIFU device exhibited an AE profile similar to that of sham treatment. There were no significant changes from baseline in laboratory values, including lipid levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 10 publications
0
50
0
1
Order By: Relevance
“…The most adverse effects of treatment were pain, ecchymosis and swelling. Post-treatment follow-up at 12 and 24 weeks revealed no significant changes in cholesterol, triglycerides, free fatty acids, markers of inflammation and liver or renal function (24). Moreover Jewell et al confirmed HIFU as a useful method for reducing waist circumference.…”
Section: Resultsmentioning
confidence: 99%
“…The most adverse effects of treatment were pain, ecchymosis and swelling. Post-treatment follow-up at 12 and 24 weeks revealed no significant changes in cholesterol, triglycerides, free fatty acids, markers of inflammation and liver or renal function (24). Moreover Jewell et al confirmed HIFU as a useful method for reducing waist circumference.…”
Section: Resultsmentioning
confidence: 99%
“…This ability of FUS to reduce fat was recognized by the cosmetic industry and is the most commercially successful use of FUS in humans, with several commercial devices on the market [344, 345]. Similarly, the use of focal thermal coagulation for the shrinkage of tissue has been investigated for skin-tightening using an FDA-approved device [346, 347].…”
Section: Future Developmentsmentioning
confidence: 99%
“…Desse modo, o grau de satisfação do paciente baseado nas mudanças estéticas ocorridas após o tratamento é um dos fatores que devem ser levados em consideração na rotina clínica. Jewell et al 20 destacam a importância do registro fotográfico em diferentes momentos, bem como a auto percepção corporal pós tratamento como método avaliativo. Porém, uma ferramenta acurada a fim de mensurar quantitativamente as alterações ocorridas é salutar para a determinação da eficácia da intervenção.…”
Section: Discussionunclassified